XVIII. dönem TBMM ve faaliyetleri (1987-1991) - Talayhan, Aliyna (My University, 2024)
TBMM, Türkiye Cumhuriyeti’nde önemli bir kurumdur. 23 Nisan 1920’de ilk meclis açılmış ve bu zamana kadar devletin en önemli kurumları arasında yerini almıştır. Yasama organı olan meclis farklı dönemlerde etkisini, farklı şekillerde gösterdi. 12 Eylül 1980 darbesinden sonra siyasette askeri kanadın etkisi hissedildi.1982 Anayasasının kabulüyle birlikte farklı partiler kurularak farklı görüşlerin temsiline izin verilmişti. 1983 seçimleriyle ANAP iktidara gelmiştir. ANAP’ın iktidara gelmesiyle XVII. Dönem TBMM başladı. 1987 seçimlerinde tekrar ANAP’ın kazanmasıyla XVIII. Dönem TBMM süreci başlamıştır. ANAP’ın ağırlığını hissettirdiği mecliste önce Başbakan daha sonra 1989 seçimleriyle Cumhurbaşkanı olan Turgut Özal’ın hem iç siyasette izlediği politika hem de dış politikası dönemin muhalif partileri tarafından eleştirildi. Turgut Özal, Yıldırım Akbulut ve Mesut Yılmaz’ın oluşturduğu hükümetler XVIII. Dönem TBMM’nin temelini oluşturmuştu. Bu dönemde yaşanan dış politikadaki gelişmeler, çıkarılan kanunlar Türk tarihinde önemli bir yere sahiptir. Bu çalışmanın amacı XVIII. Dönem TBMM’nin yapısını ve faaliyetlerini incelemektir. Kendinden önce ve sonraki meclisler çalışılmış olup, bu dönem itibariyle eksik kalmaktaydı. Eksik kalan XVIII. Dönem TBMM bu çalışma ile tamamlanmaya çalışılmıştır.

The Turkish Grand National Assembly is an important institution in the Republic of Türkiye. The first parliament was opened on April 23, 1920, and by this time it had taken its place among the most important institutions of the state. The parliament, which is the legislative body, has shown its influence in different ways in different periods. After the coup of September 12, 1980, the influence of the military wing was felt in politics. With the adoption of the 1982 Constitution, different parties were established and the representation of different views was allowed. ANAP came to power with the 1983 elections. With ANAP coming to power in the XVII. the period. The term of the Turkish Grand National Assembly has started. With ANAP winning again in the 1987 elections, XVIII. the term Turkish Grand National Assembly process has started. Turgut Özal, who became first the prime minister and then the president with the 1989 elections in the parliament, where ANAP made its presence felt, was criticized by the opposition parties of the period for both his domestic policy and foreign policy. The governments formed by Turgut Özal, Yıldırım Akbulut and Mesut Yılmaz were in the XVIII. the period. This period formed the basis of the Turkish Grand National Assembly. The developments in foreign policy and the laws enacted during this period had an important place in Turkish history. The aim of this study is the XVIII. The term is to examine the structure and activities of the Turkish Grand National Assembly. The assemblies before and after him were studied, but they were incomplete as of this period. The missing XVIII. The term of the Turkish Grand National Assembly was tried to be completed with this study.
Keywords: ANAP; Dönem; Government; History; Hükümet; Period; Political parties; Siyasi partiler; Tarih; TBMM; Turkey; Turkish Grand National Assembly; Türkiye; Türkiye Büyük Millet Meclisi; XVIII